Analysis of Citizen Science-Based Flowering Plant Diversity Worksheet Development to Improve Students’ Critical Thinking Ability - Nissa Rachmawati; Topik Hidayat; Bambang Supriatno (BIOEDUKASI, 2022)
The purpose of this study was to assess the feasibility of the developed Citizen Science-Based Flowering Plant Diversity Worksheet as well as the enhancement of students' critical thinking abilities. This was a pre-experiment with a pretest-posttest design with one group. Validator employed a four-scale validation sheet to assess the feasibility of the Citizen Science-Based Flowering Plant Diversity Worksheet based on competency, practical, knowledge construction, and the appearance of critical thinking ability. Five critical thinking ability indicators were tested: interpretation, analysis, explanation, evaluation, and inference. These indications were tested in 104 10th grade students through a critical thinking ability test before and after studying with the Citizen Science-Based Flowering Plant Diversity worksheet. Descriptive statistics were used to analyze the data. The Citizen Science-Based Flowering Plant Diversity Worksheet was found feasible (95.12%) and students' critical thinking abilities increased moderately (N-Gain = 0.56). The most notable development in critical thinking ability was in interpretation ability, while inference ability improved the least. As a result, the Citizen Science-Based Flowering Plant Diversity Worksheet may be inferred to be quite effective in improving students' critical thinking abilities.